The SNAP-25 linker supports fusion intermediates by local lipid interactions - Ahmed Shaaban; Madhurima Dhara; Walentina Frisch; Ali Harb; Ali H Shaib; Ute Becherer; Dieter Bruns; Ralf Mohrmann (eLife, 2019)
SNAP-25 is an essential component of SNARE complexes driving fast Ca2+-dependent exocytosis. Yet, the functional implications of the tandem-like structure of SNAP-25 are unclear. Here, we have investigated the mechanistic role of the acylated “linker” domain that concatenates the two SNARE motifs within SNAP-25. Refuting older concepts of an inert connector, our detailed structure-function analysis in murine chromaffin cells demonstrates that linker motifs play a crucial role in vesicle priming, triggering, and fusion pore expansion. Mechanistically, we identify two synergistic functions of the SNAP-25 linker: First, linker motifs support t-SNARE interactions and accelerate ternary complex assembly. Second, the acylated N-terminal linker segment engages in local lipid interactions that facilitate fusion triggering and pore evolution, putatively establishing a favorable membrane configuration by shielding phospholipid headgroups and affecting curvature. Hence, the linker is a functional part of the fusion complex that promotes secretion by SNARE interactions as well as concerted lipid interplay.